2016
DOI: 10.1017/s143192761601151x
|View full text |Cite
|
Sign up to set email alerts
|

Two-Color, Two-Photon Imaging at Long Excitation Wavelengths Using a Diamond Raman Laser

Abstract: Microscopy and Microanalysis, a Cambridge University Press journalthe Ti:Sapphire laser, resulting in a laser system tunable 680 nm-1200 nm it can be used for twophoton excitation of a large variety and combination of dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…To date, diamond Raman lasers have seen little use in microscopy. A Ti:S pumped diamond Raman laser has been used for asynchronous multi-color imaging in thin cell samples 24 , and a Nd:YVO 4 -pumped, picosecond diamond Raman laser emitting at 1240 nm has been demonstrated 25 , but not used for imaging. We show, for the first time, that a diamond Raman laser can generate femtosecond (~100 fs) pulse-widths at 1240 nm through pumping with an amplified ytterbium fiber source, and that the output is stable enough for routine use as a microscopy source.…”
Section: Introductionmentioning
confidence: 99%
“…To date, diamond Raman lasers have seen little use in microscopy. A Ti:S pumped diamond Raman laser has been used for asynchronous multi-color imaging in thin cell samples 24 , and a Nd:YVO 4 -pumped, picosecond diamond Raman laser emitting at 1240 nm has been demonstrated 25 , but not used for imaging. We show, for the first time, that a diamond Raman laser can generate femtosecond (~100 fs) pulse-widths at 1240 nm through pumping with an amplified ytterbium fiber source, and that the output is stable enough for routine use as a microscopy source.…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in Section 2, the 2PE wavelength at 1047 nm overlaps with the absorption band of several bio-imaging dyes. However, both Cr:Forsterite and Nd:YLF mode-locked lasers lack a wide wavelength tuning range (Trägårdh et al, 2016), which implies that fluorescent probes must be carefully chosen in order to match the small bandwidths, therefore this tends to limit biological imaging to just one colour. An example of a solid-state laser being used for in vivo applications involve a Nd:YLF laser being used to perform 2P NIR-II imaging of a stained zebrafish embryo (Wokosin et al, 1996a) (Section 3.2, Table 3).…”
Section: Nir-ii Solid-state Pulsed Lasersmentioning
confidence: 99%
“…To overcome the drawback of limited excitation wavelengths of such solid-state lasers, multi-colour 2P imaging can instead be achieved by using two tunable lasers in tandem, although this is a relatively high-cost solution. Other solutions have been found in utilising the second Stokes shift to extend output wavelengths in Ti:Sapphire laser systems, or in methods such as phase-shaping (Brenner et al, 2013;Trägårdh et al, 2016).…”
Section: Nir-ii Solid-state Pulsed Lasersmentioning
confidence: 99%
“…Currently, multi-color two-photon microscopy imaging is a research hotspot in biomedical photonics, the reported multi-color two-photon microscopy mainly includes the following implementation methods. On one hand, multiple femtosecond lasers are used as excitation sources to excite different fluorescence probes, however, it will make the optical path of the imaging system complicated, expensive, and reduce the stability of the system [7][8][9]. On the other hand, a new type of pulsed laser can be developed as a light source, which can simultaneously excite a variety of fluorescent dyes.…”
Section: Introductionmentioning
confidence: 99%